Self-interaction free local exchange potentials applied to metallic systems. (10th August 2017) - Clark, S J; Hollins, T W; Refson, K; Gidopoulos, N I
Abstract: We extend the formalism of local exchange methods to calculate and investigate the electronic structure of metals. It is well-known that the Hartree–Fock method when applied to metals shows unphysical behaviour, however the accurate treatment of exchange via DFT's exact exchange method and using our local Fock exchange method can be used to describe metallic band structures accurately.